Managed eaudiobook - Callihan, Kristen (VIP, 2021)
It started off as a battle of wits. Me: the ordinary girl with a big mouth against him : the sexy bastard with a big . . . ego. I thought I'd hit the jackpot when I was upgraded to first class on my flight to London. That is, until he sat next to me. Gabriel Scott: handsome as sin, cold as ice. Nothing and no one gets to him. Ever. He's a legend in his own right, the manager of the biggest rock band in the world, and an arrogant ass who looks down his nose at me. I thought I'd give him hell for one, long flight. I didn't expect to like him. I didn't expect to want him. But the biggest surprise? He wants me too. Only in a way I didn't see coming. If I accept his proposal, I leave myself open to falling for the one man I can't manage. But I'm tempted to say yes. Because the real man beneath those perfect suits and that cool façade just might be the best thing that's ever happened to me. And I just might be the only one who can melt the ice around his heart. Let the battle begin . . . Contains mature themes.